KARAKTERISTIK SENSORIS SUSU KETAPANG (Terminalia Catapa L.) SUBTITUSI SUSU KEDELAI HIGH PROTEIN - Maghfiroh Maghfiroh; Achmad Alfan Wijaya; Elis Sa'adah; Moh Iqbal Arisa Valla; Faizal Romadhon (AGROINTEK, 2014)
Milk is a food that is essential to human life because milk contains nutrients, especially protein, vitamins and minerals. Milk not only from animal materials but also made from plant materials such as legumes including soybeans. The purpose of this study was to determine the sensory characteristics of ketapang milk made by substituing soy with ketapang seed in the making of soy milk. Experimental designwasarranged according to Response Surface Methodology (RSM) using 2-factorsand 5 levels in each factor. The first factor was concentration of soybean (0%, 10%, 15% , 20%, and 25%) and the second factor was concentration of Na-CMC (0%, 0.5%, 1%, 1.5%, 2%). The results showed that the best characteristics possessed by the best formula contained in the treatment with the highest soy concentration of 25% (75% seed ketapan and the addition of Na-CMC concentration lows of 0%, but in the manufacture of soy milk ketapan added Na-CMC 0.05% since without the addition of Na-CMC will form a precipitate in the milk. The results of the proximate test showed that the levels of protein in every 100 grams of material was 18.058%.